GMAT Question of the Day - Daily to your Mailbox; hard ones only

 It is currently 18 Apr 2019, 08:03

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# (2 + x)(2 + y) – (2 + x) – (2 + y) =

Author Message
TAGS:

### Hide Tags

Math Expert
Joined: 02 Sep 2009
Posts: 54368
(2 + x)(2 + y) – (2 + x) – (2 + y) =  [#permalink]

### Show Tags

31 May 2017, 01:40
00:00

Difficulty:

5% (low)

Question Stats:

98% (01:08) correct 2% (00:56) wrong based on 63 sessions

### HideShow timer Statistics

$$(2 + x)(2 + y) – (2 + x) – (2 + y) =$$

(A) 2y
(B) xy
(C) x + y
(D) x – y
(E) x + y + xy

_________________
DS Forum Moderator
Joined: 22 Aug 2013
Posts: 1443
Location: India
Re: (2 + x)(2 + y) – (2 + x) – (2 + y) =  [#permalink]

### Show Tags

31 May 2017, 04:14
(2+x)(2+y) = 4 + 2x + 2y + xy

Thus, (2+x)(2+y)–(2+x)–(2+y) = 4 + 2x + 2y + xy - 2 -x -2 - y = (x + y + xy)

Senior PS Moderator
Joined: 26 Feb 2016
Posts: 3386
Location: India
GPA: 3.12
Re: (2 + x)(2 + y) – (2 + x) – (2 + y) =  [#permalink]

### Show Tags

31 May 2017, 07:21
We need to find out the value of this expression
(2+x)(2+y)–(2+x)–(2+y)
Substituting values x=y=1

We get 9 - 3 - 3 = 3

Of the available answer options, only Option E gives us the same value as the expression.
_________________
You've got what it takes, but it will take everything you've got
Target Test Prep Representative
Status: Founder & CEO
Affiliations: Target Test Prep
Joined: 14 Oct 2015
Posts: 5772
Location: United States (CA)
Re: (2 + x)(2 + y) – (2 + x) – (2 + y) =  [#permalink]

### Show Tags

01 Jun 2017, 17:28
Bunuel wrote:
$$(2 + x)(2 + y) – (2 + x) – (2 + y) =$$

(A) 2y
(B) xy
(C) x + y
(D) x – y
(E) x + y + xy

Let’s simplify the given expression:

(2 + x)(2 + y) - (2 + x) - (2 + y)

4 + 2x + 2y + yx - 2 - x - 2 - y

x + y + yx

_________________

# Scott Woodbury-Stewart

Founder and CEO

Scott@TargetTestPrep.com
122 Reviews

5-star rated online GMAT quant
self study course

See why Target Test Prep is the top rated GMAT quant course on GMAT Club. Read Our Reviews

Manager
Joined: 18 Jan 2017
Posts: 128
Re: (2 + x)(2 + y) – (2 + x) – (2 + y) =  [#permalink]

### Show Tags

17 Jul 2017, 10:44
Bunuel wrote:
$$(2 + x)(2 + y) – (2 + x) – (2 + y) =$$

(A) 2y
(B) xy
(C) x + y
(D) x – y
(E) x + y + xy

=====

All we need to do is simplify this expression.

Multiply (2 + x)(2 + y) using FOIL. [First Outer Inner Last] and simplify

(2 + x)(2 + y) - (2 + x) - (2 + y)
4 + 2x + 2y + yx - 2 - x - 2 - y
x + y + yx

_____________
_________________
A KUDO = A Thank-you. If this post helped you, please send a KUDO across.

YOU CAN LEARN ANYTHING!
MY GMAT BLOG ---> https://gmatclub.com/forum/a-fitness-mat-some-music-few-books-and-the-gmat-245808.html
Manager
Joined: 19 Jul 2017
Posts: 85
Location: India
Concentration: General Management, Strategy
GPA: 3.5
Re: (2 + x)(2 + y) – (2 + x) – (2 + y) =  [#permalink]

### Show Tags

27 Aug 2017, 04:05
took (2+x) common from the first two elements

so (2+x)(2+y) -(2+x)-(2+y)= (2+x) ((2+y)-1) -(2+y)
=(2+x)(1+y)-(2+y)
=2+2y+x+xy-2-y
=x+y+xy
Re: (2 + x)(2 + y) – (2 + x) – (2 + y) =   [#permalink] 27 Aug 2017, 04:05
Display posts from previous: Sort by